(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Skin disorders are increasingly prevalent today due to modern lifestyles and stress. Ayurveda references skin diseases primarily under the category of Kushtha, with Vicharchika (eczema) being one that is predominantly influenced by Kapha. While steroid therapies are commonly used, they can cause side effects. Therefore, exploring new topical treatments may help reduce the need for long-term steroid use. Aim: To assess the efficacy of Japapatryadi Tail local application and Amritadi Kwath in Vicharchika (eczema). Materials and Methods: This study involved an open-label clinical trial with 30 patients diagnosed with Vicharchika (eczema). The participants were treated with a topical application of Tail and an oral dosage of Kwath for 50 days. The effectiveness of the treatment was evaluated by assessing changes in the following clinical parameters before and after the intervention: Kandu (itching), Daha (burning sensation), Strava (oozing), Rukshata (dryness), Pidikotpatti (eruptions), Vaivarnyata (discoloration), Rajii (thickening of skin). Data were collected at baseline (day 0) and at the end of the treatment period. The results were analyzed using the paired ‘t’ test to determine the significance of the observed changes. Results: The topical application of Japapatryadi Tail and Amritadi Kwath was found to be highly effective in reducing the symptoms of Vicharchika (eczema). Conclusion: Japapatryadi Tail and Amritadi Kwath could be used in symptomatic relief of Vicharchika (eczema), and also repairs and enhances the damaged skin.